Phytoplankton diversity in Adriatic ports: Lessons from the port baseline survey for the management of harmful algal species. (October 2019) - Mozetič, Patricija; Cangini, Monica; Francé, Janja; Bastianini, Mauro; Bernardi Aubry, Fabrizio; Bužančić, Mia; Cabrini, Marina; Cerino, Federica; Čalić, Marijeta; D'Adamo, Raffaele; Drakulović, Dragana; Finotto, Stefania; et al.
Abstract: An inventory of phytoplankton diversity in 12 Adriatic ports was performed with the port baseline survey. Particular emphasis was put on the detection of harmful aquatic organisms and pathogens (HAOP) because of their negative impact on ecosystem, human health, and the economy. Phytoplanktonic HAOP are identified as species, either native or non-indigenous (NIS), which can trigger harmful algal blooms (HAB). A list of 691 taxa was prepared, and among them 52 were classified as HAB and five as NIS. Records of toxigenic NIS ( Pseudo-nitzschia multistriata, Ostreopsis species including O. cf. ovata ) indicate that the intrusion of non-native invasive phytoplankton species has already occurred in some Adriatic ports. The seasonal occurrence and abundance of HAOP offers a solid baseline for a monitoring design in ports in order to prevent ballast water uptake and possible expansion of HAOP outside their native region. Highlights: Port baseline survey of phytoplankton was carried out in 12 Adriatic ports. 691 taxa were identified and typical seasonal community patterns were outlined. Pseudo-nitzschia, Alexandrium, and Dinophysis were the most frequent and abundant HAB. P. multistriata and Ostreopsis cf. ovata are NIS of the greatest harmful potential. The phytoplankton list provides grounds for monitoring HAOP in Adriatic ports.